A Socio-pragmatics Study: Flouting of Conversational Maxims Found in “Bence” Traditional Market, Kediri - Mohammad Muhyidin (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2020)
The study focuses on the flouting of conversational maxims in one of the traditional markets in Kediri. This study focuses on the types of flouted maxims, and the situations where the flouted maxims cause misunderstanding between the sellers and the buyers in the trade of interaction. This research is conducted by using a descriptive qualitative approach. The data are utterances between sellers and buyers. The theory which the writer used is based on the theory of Cooperative Principles, proposed by Grice (1975), which establishes four maxims, those are the maxim of quality, the maxim of quantity, the maxim of relation and maxim of manner. The data is collected by recording the conversation in the trade transaction. The data is also collected by noting the conversation and transcript it. The finding shows that there are many flouted maxims found in interaction practices between the seller and buyer. The writer’s analysis show that all kinds of maxims are flouted mostly buy the seller. Those are maxim of quantity, maxima of quality, maxims of relevance and maxim of manner. Thus, it may happen because between the seller and the buyer do not fulfil the rules of cooperative principles. The writer concludes there are some condition which make the participants in the trade interaction have to flout the maxims. Due to the fact that the conversation still run well without any misunderstanding.